(untitled) (Journal of the College of Education for Women, 2019)
I noticed a researcher while working in the kindergarten that there is a group ofparameters resort to the use of different methods may be some undesirable and someundesirable So felt researcher detection methods used parameters Riyadh in the face of thepressures of life, being engaged in kindergarten eligibility, governmental or being married orunmarried, as well as educational attainment for this parameter.To achieve the objectives of the research: -The researcher prepare a scale methods face the pressures of life of the parametershave been confirmed the veracity of the paragraphs of the scale of the presentation to a groupof experts in this area, and extracted power discriminatory clauses scale and extracted stabilityof each style, and the scale of the five methods (Calendar positive (5) vertebrae, avoid andescape from (17), paragraph, accept responsibility (6) vertebrae, resorting to religion (9)vertebrae, withdrawal (7) paragraphs).After processing the data statistically research found the following results:1- That Riyadh parameters using all the pressures of life styles.2 - The Riyadh parameters of married and unmarried women using the withdrawal method andparameters using a method married escape and avoidance problem more parameters unmarriedwomen.3 - that Riyadh parameters using all five methods, according to the specialization variable4 - The civil kindergarten teachers more commonly used method of escape and avoid the problem ofparameters Riyadh-governmental organizations.